The Dynamics of Interpersonal Communication between Parents and Adolescents in the Digital Era: A Literature Review - Syadza Hanifa; Nanang Trenggono; Abdul Firman Ashaf; Nanda Utaridah (Universitas Islam Negeri Raden Intan Lampung, 2025)
The rapid development of digital technology has brought significant changes to the dynamics of interpersonal communication between parents and adolescents. The presence of digital media in family life has not only shifted interaction patterns from face-to-face communication to technology-mediated communication, but has also generated various challenges, including conflict, differences in perception, and the need for communication adjustment between parents and adolescents. This article aims to analyze the dynamics of parent–adolescent interpersonal communication in the digital era through a literature review approach. This study employs a qualitative descriptive literature review method. Data are collected from relevant scholarly sources, including national and international journal articles, academic books, and scientific publications that discuss family communication and adolescent digital media use. Data analysis is conducted using content analysis to identify major themes related to changes in communication patterns, parent–adolescent conflict, negotiation processes, and the maintenance of emotional closeness within families. The findings indicate that digital media plays an ambivalent role in family communication. Poorly managed digital media use may intensify conflict between parents and adolescents, while adaptive and dialogic interpersonal communication can strengthen emotional closeness. Therefore, the quality of interpersonal communication remains a key factor in maintaining harmonious parent–adolescent relationships in the digital era.